PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS SMS GATEWAY PADA ONLINE SHOP TOKOFARAH - Arfiani Nur Khusna (Telematika, 2016)
SMS applications has become a promising business opportunities in the consumer and industrial markets in the world. One part that can not be separated from the SMS business is the role of an SMS Gateway, a system used by service providers to send and receive SMS automatically. Online shop tokofarah an online web business venture engaged in the production and sales of baby clothes and children. The problems that exist in the online shop tokofarah is the absence of communication between the customer and tokofarah thus reduced customer loyalty, customers are unaware of the latest promos and discounts, so the application of CRM (Customer Relationship Management) is very necessary to help communication. Alternative solutions in addition to implementing CRM also develop and implement SMS technology as a service via SMS Gateway online. Where customers can easily find information on the latest promos and discounts, customers can simply type a certain key word and send it to a specific number that has been provided, the store can also inform customers about the latest promos and products through SMS brodcast. In this study, using Gammu as tools liaison between the device with a computer modem. Making the program using the programming language PHP as an interface, a database maker MySQL tools. The results of the implementation of the concept of SMS Gateway technology is that it can provide convenience for online customers shop tokofarah in knowing the promo and the latest product information and can order via SMS.